Trabajo experimental como estrategia metodológica para lograr aprendizajes significativos en Ciencias Naturales. Año lectivo 2021-2022 - Gaona Sarango, José Luis (2023)
In current education, it is important that the teacher has the ability to propose alternatives that solve the learning gaps that can be generated by the fact that students do not complement, through the practice, the theoretical studied, hence, through the present research, an alternative focused on experimental work, whose aim was: To enhance the significative learning achievement in Natural Science, through the experimentation with home material, that allow the teaching and learning process with students of eight grade of basic education of “27 de febrero” High school, academic year 2021 – 2022. Regarding the applied methodology, it is inductive focused on qualitative approach, along it, relevant characteristics were determined, around the implementation of innovative methodology strategies of teaching and learning, likewise, it is participative action research, because once the problem was defined, which is the lack of materials and instruments, that allow to make experimental practices, it was established the work methodology with home materials. In addition, according to the temporality, this is transversal research, due to the proposal application for the intervention, it was executed in a determined time into the academic period 2021 -2022. The achieved results, stated that the experimentation with the use of home material, it makes it possible to deepen the theory and increase the interest of students to participate and observe experiments. Thus, it is determined that the application of innovative resources like homemade material, promotes the building of significative learning in students, in Natural Science. Keywords: Academic performance, homemade material, Constructivism, significative learning